Writing the legal record : law reporters in nineteenth-century Kentucky - Metzmeier, Kurt X. (University Press of Kentucky, 2017)
Any student of American history knows of Washington, Jefferson, and the other statesmen who penned the documents that form the legal foundations of our nation, but many other great minds contributed to the development of the young republic's judicial system -- figures such as William Littell, Ben Monroe, and John J. Marshall. These men, some of Kentucky's earliest law reporters, are the forgotten trailblazers who helped establish the foundation of the state's court system. In Writing the Legal Record: Law Reporters in Nineteenth-Century Kentucky, Kurt X. Metzmeier provides portraits of the men whose important yet understudied contributions helped create a new common law inspired by English legal traditions but fully grounded in the decisions of American judges. He profiles individuals such as James Hughes, a Revolutionary War veteran who worked as a legislator to reform confusing property laws inherited from Virginia. Also featured is George M. Bibb, a prominent U.S. senator and the secretary of the treasury under President John Tyler. To shed light on the pioneering individuals responsible for collecting and publishing the early opinions of Kentucky's highest court, Metzmeier reviews nearly a century of debate over politics, institutional change, human rights, and war. Embodied in the stories of these early reporters are the rich history of the Commonwealth, the essence of its legal system, and the origins of a legal print culture in America.